Analysis of Students’ Interest in Utilizing Educational Applications During Leisure Time Using the Technology Acceptance - Hoiriah Hoiriah; Haddiel Fuad; Aspari Aspari (Jurnal Multidisiplin Sahombu, 2026)
The rapid development of digital technology has created various new opportunities in the education sector, particularly in supporting learning activities outside school hours. This study aims to examine students’ interest in using digital educational applications beyond formal classroom time by applying the Technology Acceptance Model (TAM). The model emphasizes three key variables: Perceived Usefulness, Perceived Ease of Use, and Behavioral Intention. The study was conducted at a junior high school in South Tangerang using a quantitative research approach. Data were collected through the distribution of Google Form–based questionnaires to 123 respondents who met the research criteria and were analyzed using validity and reliability tests, as well as t-tests and F-tests, with SPSS software. The results indicate that perceived usefulness and perceived ease of use have a significant influence on students’ interest in using digital educational applications, both simultaneously and partially. An F-value of 47.962 with a significance level of 0.000 demonstrates that the independent variables positively affect students’ interest in using digital educational applications. These findings confirm the importance of educational applications as alternative learning media and highlight the need for educational institutions to optimize the use of digital technology in supporting students’ independent learning processes.